2006
DOI: 10.1097/01.bcr.0000195093.36328.ab
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Implications of Working in a Burn Unit

Abstract: Burnout is a syndrome that has been characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment associated with chronic occupational stressors. The purpose of this study was to determine the prevalence of burnout in healthcare professionals involved in primary burn care and to gain an understanding of the stressors and pleasures they experience. A cross-sectional survey was administered between February and March 2004 to healthcare professionals working in the burn unit (BU, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…When compared with nurses across Canada, dietitians in Ontario had more encouraging EE, PA and DP scores (Laschinger & Leiter, 2006). Murji et al (2006) reported that 24% of healthcare professionals working in the critical care and burn units of an Ontario hospital had high EE scores, and 35% experienced low levels of PA. Nurses, occupational therapists, physicians, physical therapists, social workers and respiratory therapists were included in the sample. Cohen & Gagin (2005) reported that hospital social workers in Israel have EE scores in the range 22-23.9, DP scores in the range 5.29-7.36 and PA scores in the range 31.40-32.83.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with nurses across Canada, dietitians in Ontario had more encouraging EE, PA and DP scores (Laschinger & Leiter, 2006). Murji et al (2006) reported that 24% of healthcare professionals working in the critical care and burn units of an Ontario hospital had high EE scores, and 35% experienced low levels of PA. Nurses, occupational therapists, physicians, physical therapists, social workers and respiratory therapists were included in the sample. Cohen & Gagin (2005) reported that hospital social workers in Israel have EE scores in the range 22-23.9, DP scores in the range 5.29-7.36 and PA scores in the range 31.40-32.83.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other types of physicians, critical care physicians have the highest prevalence of BOS, followed closely by emergency medicine physicians (11). There is a paucity of data on the prevalence of BOS in other critical care health-care professionals, such as social workers, and respiratory, physical, occupational, or speech therapy health-care professionals (31). In one study, nursing assistants were more likely to have BOS compared with other types of critical care health-care professionals (8).…”
Section: Prevalence Of Bos In Critical Care Health-care Professionalsmentioning
confidence: 99%
“…31 In one study, nursing assistants were more likely to have BOS compared with other types of critical care health care professionals. 8 …”
mentioning
confidence: 99%